1996
DOI: 10.1007/bf00037796
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration of chickpea (Cicer arietinum L.): Stimulation of direct organogenesis and somatic embryogenesis by thidiazuron

Abstract: In vitro regeneration in chickpea (Cicer arietinum L.) was achieved by direct culture of mature seeds on Murashige and Skoog (MS) medium supplemented with either N-phenyl-N' (-1,2,3-thidiazol-5-yl) urea (thidiazuron, TDZ) or N6-benzylaminopurine (BAP). Multiple shoots formed de novo without an intermediary callus phase at the cotyledonary notch region of the seedlings within 2 to 3 weeks of culture initiation. TDZ was found to be more effective compared to BAP as an inductive signal of regeneration. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 22 publications
5
38
2
2
Order By: Relevance
“…It has been observed for various legumes that high concentration of cytokinin stimulated callus and subsequently shoot bud formation (Malik & Saxena, 1992;Dorneles et al, 1994), increased their survival (Dorneles et al, 1994) but also inhibited shoot growth (Thomé et al 1995). Other studies with legumes in vitro (Dewan et al, 1992;Mohamed et al, 1992;Murthy et al, 1996) have determined the need of cytokinin for shoot differentiation and bud multiplication. The percentage of buds elongating into shoot regenerants was 68.2% in this work, compared to values of 81 and 94% obtained by Murthy et al (1996) with Cicer arietinum.…”
Section: Results and Discussion A) Tissue Culturementioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed for various legumes that high concentration of cytokinin stimulated callus and subsequently shoot bud formation (Malik & Saxena, 1992;Dorneles et al, 1994), increased their survival (Dorneles et al, 1994) but also inhibited shoot growth (Thomé et al 1995). Other studies with legumes in vitro (Dewan et al, 1992;Mohamed et al, 1992;Murthy et al, 1996) have determined the need of cytokinin for shoot differentiation and bud multiplication. The percentage of buds elongating into shoot regenerants was 68.2% in this work, compared to values of 81 and 94% obtained by Murthy et al (1996) with Cicer arietinum.…”
Section: Results and Discussion A) Tissue Culturementioning
confidence: 99%
“…Other studies with legumes in vitro (Dewan et al, 1992;Mohamed et al, 1992;Murthy et al, 1996) have determined the need of cytokinin for shoot differentiation and bud multiplication. The percentage of buds elongating into shoot regenerants was 68.2% in this work, compared to values of 81 and 94% obtained by Murthy et al (1996) with Cicer arietinum. The choice of MS culture medium to establish a protocol for B. forficata in vitro plant regeneration was due to its frequent use and good success for shoot induction in tissue culture studies of legumes trees like Swartzia madagascariensis (Berger & Schaffner, 1995) and other species of Bauhinia genus (Upreti & Dhar, 1996).…”
Section: Results and Discussion A) Tissue Culturementioning
confidence: 99%
“…The modulation of endogenous ABA and GA by TDZ was also reported (Murthy et al, 1996;Murch et al, 1999). But unfortunately, no progress was made in this field later on.…”
Section: Involvement Of Phytohormonesmentioning
confidence: 99%
“…Tapan et al (1998) observed the callus of tea overgrowth and later necrosis when the responsive explants were continuously grown on the medium containing TDZ. The deleterious effect of the continued presence of TDZ on the growth and multiplication have been reported for chickpea (Murthy et al, 1996), Pisum sativum (Bohmer et al, 1995), Anoectochilus formosanus (Ket et al, 2004), Rauvolfia tetraphylla (Faisal et al, 2005) and Psoralea corylifolia (Faisal and Anis, 2006). Chitra and Padmaja (2005) reported that only few buds derived leaves of mulberry developed into shoots of 0.5 to 1.5 cm at the end of 30 days, and growth of the rest of the adventitious shoot buds remained arrested on medium containing 18.17 and 22.7 mM TDZ.…”
Section: Effects Of Concentrationmentioning
confidence: 99%
“…TDZ has been used to elicit multiple shoot formation in a broad range of plant species (Malik and Saxena 1992a,b), and somatic embryogenesis in a few crop species Lu 1993). While other studies indicated successful utilization of cytokinins for somatic embryogenesis not only in pigeon pea (Patel et al 1994;Sreenivasu et al 1998;Mohan and Krishnamurthy 2002;Chandra et al 2003;Singh et al 2003) but also other leguminous crops (Maheswaran and Williams 1984;Gill and Saxena 1992;Malik and Saxena 1992b;Murthy et al 1996). The MS medium comprising TDZ and BAP was found less effective for globular embryo formation with glucose than sucrose.…”
Section: Somatic Embryogenesismentioning
confidence: 99%